IMPLEMENTATION OF INCLUSIVE EDUCATION: DO PARENTS REALLY MATTER? - Afolabi, Olusegun; Mukhopadhyay, Sourav; Nenty, H. Johnson (Specijalna edukacija i rehabilitacija, 2013)
It has long been ascertained thatthe application of a family centered perspectives tolearning is a positive strategy toward implementation of inclusive education worldwide. Similarly, research also confirmed that meaningful parent’s involvement is highly recognized as the most important ingredient for successful inclusive practice. This article critically explores and review research literature on the relevance and usefulness of family involvement to the implementation of inclusive education. The article planned to increase our knowledge and understanding of the crucial role that engaging with families of learners in needs might have on their learning, and look at earlier study relating tothe major effects of parental involvement in inclusion. Moreover, the article also paid particular attention to how culture, ethnicity, socioeconomic background, and family characteristics influence the level of school –parent’s partnership in inclusive settings. Finally, findings revealed parents as a social actor, and that their involvement islink with positive outcomes for learners with exceptional needs in inclusive settings. Keywords: parental involvement, inclusive education, parental perception, family involvement